Engaging dissonance : developing mindful global citizenship in higher education - Lee, Amy, 1967-; Williams, Rhiannon D. (Innovations in higher education teaching and learning ;, 2017)
This volume explores the internationalization of higher education in the context of global citizenry and intercultural competencies. It focuses on presenting dissonance as a means to facilitating students openness to complexity and development of intercultural skills or their experiences in the classroom. This volume provides educators with a conceptual and practical resource that focuses on the critical role of cognitive complexity/dissonance in the education of global citizens and the enactment of intercultural pedagogy. Addressing the tensions and complexities of varying viewpoints and experiences with equity and intercultural work will challenge readers to think critically about the implications of individual practice as well as unit and institutional structures and support in relation to desired college equity and intercultural goals.